Antihemophilic Factor: Its Presence in Fibrinogen, Assay Problems and the Stability of Lyophilized AHF-Fibrinogen Preparations - Baumgarten, Werner; Sanders, Benjamin E.; Belkin, Benita D; Pagenkemper, Frank E; Albers, William G; Ciminera, Joseph L (Thrombosis and Haemostasis, 1963)
The thromboplastin generation test of Biggs et al. and of Pitney, and adopted by Surgenor for the assay of antihemophilic factor activity in lyophilized preparations of human fibrinogen, has been modified to yield a selfcontained statistically valid assay. This procedure was designed to serve primarily as a control procedure. The AHF activity of production lots of human fibrinogen was assayed, and the stability of AHF under different conditions of storage was determined.The procedure described in this paper is a satisfactory control procedure for AHF potency testing. In the absence of a generally recognized unit of AHF potency, it would seem most helpful to the clinician to have the potency related to the average activity in fresh normal human plasma.